2009
DOI: 10.1100/tsw.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Erectile Dysfunction: Is Androgen Deficiency the Common Link?

Abstract: Obesity is associated with increased risk of erectile dysfunction (ED); however, the underlying causes of ED in obese individuals remain poorly defined. The aim of this review is to discuss the evidence available on the relationship between obesity and ED. A search of published studies in PubMed from 1970 through 2009 was conducted, and relevant articles were evaluated and discussed.Visceral obesity is a public health threat, and is associated with increased risk of diabetes, vascular disease, endothelial dysf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 82 publications
0
14
0
1
Order By: Relevance
“…The results show that IgG could potentially be associated with ED risk, after adjusting for age. Meanwhile, in this analysis, a significant association between ED and metabolic syndrome, obesity, and so on was again identified [31]. In addition, seven genes [platelet-activating factor receptor (PTAFR), interleukin 27 (IL27), CD37 molecule (CD37), CD40 molecule (CD40), interleukin 7 receptor (IL7R), proteasome subunit, beta type, 9 (PSMB9), and chemokine (C-X-C motif) receptor 3 (CXCR3)] related to humoral immunity, which might be vital in inducing ED, were analyzed with SKAT.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The results show that IgG could potentially be associated with ED risk, after adjusting for age. Meanwhile, in this analysis, a significant association between ED and metabolic syndrome, obesity, and so on was again identified [31]. In addition, seven genes [platelet-activating factor receptor (PTAFR), interleukin 27 (IL27), CD37 molecule (CD37), CD40 molecule (CD40), interleukin 7 receptor (IL7R), proteasome subunit, beta type, 9 (PSMB9), and chemokine (C-X-C motif) receptor 3 (CXCR3)] related to humoral immunity, which might be vital in inducing ED, were analyzed with SKAT.…”
Section: Resultsmentioning
confidence: 53%
“…This cross-sectional analysis of five immune elements (C3, C4, IgA, IgG, and IgM) and ED risk was conducted based on a population health survey. In the essential analysis, we found that age, obesity, drinking, educational status, and hyperglycemia could be associated significantly with ED risk, as shown in recent studies [31][32][33]. In order to discover the tendency of morbidity with age, we presented the relationship by intuitively drawing a curve chart.…”
Section: Immune Substances Associated With Edmentioning
confidence: 94%
“…Any factor that affects endothelial dysfunction and impairs endothelial nitric oxide release and the integrity of the vascular bed will certainly contribute to ED, as an erection depends on hemodynamics and vascular health. Obesity is furthermore associated with reduced plasma testosterone levels, thereby contributing to hypogonadism and ED [14,46]. In addition, there are reported relationships between low serum testosterone concentrations and ED in obese patients and those with metabolic syndrome and type II diabetes mellitus.…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…The risk of ED is even higher when diabetes is associated with obesity (Feeley and Traish, 2009). Diabetes and obesity are the most common risk factors for ED (Bacon et al, 2006;Giugliano et al, 2010) because of their deleterious effects on the vasculature (Tamler, 2009).…”
Section: Introductionmentioning
confidence: 99%